Moonstruck [videorecording (DVD)] - Jewison, Norman, 1926-; Jewison, Norman, 1926-; Cher, 1946-; Cage, Nicolas, 1965-; Gardenia, Vincent; Dukakis, Olympia; Aiello, Danny, 1933-2019- (MGM Home Entertainment ; Distributed by Sony Pictures Home Entertainment, 2006)
A superstitious Brooklyn widow is ready to get married again. Only this time, she plans on doing it right - even if she has to say "yes" to a man she doesn't really love. When she unexpectedly falls in love with her fiancé's estranged brother Ronny, what happens next is a wonderful romantic complication.